A New Algorithm and Asymptotical Properties for the Deadlock Detection Problem for Computer Systems with Reusable Resource Types - Li, Youming; Cook, Robert (Advances and Innovations in Systems, Computing Sciences and Software Engineering, 2007)
We study the classical problem of deadlock detection for systems with n processes and d reusable resource types, where d≪n. We present a novel algorithm for the problem. The algorithm enjoys two properties. First, its cost is n/log(n) times sm aller than that of the well-known Dijkstra’s algorithm, when d=O(log(n)). Secondly, its data structures are simple and easy to maintain. In particular, the algorithm employs no graph or tree based data structures. We also derive a linear-time algorithm when d and the resource requests are bounded by constants. The linear-time algorithm is asymptotically optimal. The algorithms are applicable to improving the Banker’s algorithm for deadlock avoidance. Categories and Subject Descriptors: D.4.1 Operating Systems: Process Management; General Terms: Deadlock, algorithms, performance